Do the secreted molecules of gut bacterium Faecalibacterium prausnitzii inhibit the fat accumulation in hepatocytes in vitro? - Vanhatalo, Sanja (fi=Turun yliopisto|en=University of Turku|, 2016)
Non-alcoholic fatty liver disease (NAFLD) is a metabolic disorder in which fat accumulates in liver without excessive alcohol use. NAFLD is a disease in which distortions in gut microbiota seems to play an important role. In previous studies this research group has discovered that the abundance of gut bacterium Faecalibacterium prausnitzii is lower in individuals with high hepatic fat content. In healthy human gut F. prausnitzii is one of the most abundant bacterial species. The main aim for this project was to find out does the growth media of F. prausnitzii possess beneficial effects on hepatocytes in vitro. This work also surveyed dietary fibers that could stimulate the growth of F. prausnitzii. As a model for fatty liver, human hepatocyte-derived cell line HepG2 was used and the fat accumulation was induced with the mix of oleic-palmitic acid. The growth media supernatant of F. prausnitzii was applied on the HepG2 cells together with oleic-palmitic acid mix. To quantify the amount of intracellular fat, Oil Red O staining was used. F. prausnitzii (ATCC27766) was cultured in anaerobic chambers. The effects of various fibers were studied by following changes in optical density at 600 nm. The growth media supernatant of F. prausnitzii did not inhibit the HepG2 fat accumulation in vitro. This indicates that the positive effects of F. prausnitzii on liver are not necessarily directly mediated. However, to confirm this, the method requires further optimization. We were able to identify a fiber that clearly stimulates the growth of F. prausnitzii. This fiber can be possibly used to increase the abundance of F. prausnitzii in the gut.